Comparative study on square and rectangular UHPFRC-Filled steel tubular (CFST) columns under axial compression. (December 2021) - Yang, Yekai; Wu, Chengqing; Liu, Zhongxian; Qin, Yuan; Wang, Weiqiang
Abstract: This paper presents an experimental study on the axial performance of square/rectangular concrete-filled steel tubular (CFST) columns. A total of 34 specimens, classified as four groups, were fabricated and tested under uniaxial compression. The failure modes, axial stress–strain curves, ultimate axial stress, and ductility were analysed in detail considering the effect of the steel ratio, steel fibre addition, concrete type, cross-section type, and size of the specimens. Further, the confinement index ( ξ ) and strength index (SI) was discussed. The obtained findings revealed that the ultimate axial stress of CFST columns was increased by increasing the thickness of the steel tube and adding steel fibres to the concrete mixture. When the steel ratio, steel tube thickness, and specimen height were the same, the type of cross-section (the square and the rectangular section) exhibited an insignificant effect on the axial stress–strain of the CFST column. Finally, a formula was proposed to estimate the ultimate axial stress of both square and rectangular CFST columns, with the concrete core strength ranging from 70 MPa to 150 MPa.